Peran Bimbingan Rohani Dalam Menumbuhkan Spiritual Penerima Manfaat Di Sentra “Margo Laras” Di Pati - Arum; Kawakib, Nurul; Jamaluddin Muqoffi, Ahmad; Nasihah, Dina; Aryanti, Nisya (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2025)
Abstract : This study aims to determine the role of spiritual guidance in fostering the spiritual strength of beneficiaries at the Pati “Margo Laras” Center. Spiritual guidance is one of the services provided to help beneficiaries to have inner peace, discipline in worship, and better behavioral changes in independence in carrying out activities. This research uses descriptive qualitative methods, with data collection techniques through observation, interviews, and documentation. The results showed that spiritual guidance has a positive impact in shaping a stronger spiritual attitude, such as increased motivation to worship, the emergence of a sense of calm and patience, and self-awareness in living life Activities such as congregational prayer, reading the Qur'an, and religious tausiyah are effective media in fostering mental and emotional beneficiaries This guidance also helps them in the process of social adaptation and instills moral and religious values as a provision for life after the rehabilitation period. Thus, spiritual guidance plays an important role in supporting the recovery process and overall spiritual strengthening of beneficiaries. Keywords: Spiritual Guidance; Spiritual; Beneficiaries; Social Rehabilitation. Abstrak : Penelitian ini bertujuan untuk mengetahui peran bimbingan rohani dalam menumbuhkan kekuatan spiritual penerima manfaat di Sentra